Optimalisasi Strategi Promosi Museum Balanga: Meningkatkan Kunjungan Wisatawan Mancanegara melalui Budaya Dayak Berkelanjutan - Jeanita Remilka Tabita; Maya Julia; Acep Kurniawan; Cyntia Lupita Sari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine and formulate the most effective promotional strategies to increase the number of foreign tourist visits to the Balanga Museum by developing Dayak culture in a sustainable manner. This study uses a descriptive qualitative approach, with data obtained through in-depth interviews, observations, and documentation studies, which are then analyzed using the sustainable tourism framework from the World Tourism Organization (UNWTO), the 7P Marketing Mix, and SWOT analysis. This study shows that the museum's current promotional strategies are still too focused on the domestic market and have not optimized the use of digital marketing, multilingual content, and international collaboration, resulting in limited global exposure to Dayak culture. The main obstacles include limited promotional resources and low levels of digitization. There are opportunities for development through the implementation of virtual tour-based promotions, the development of multilingual digital content, and global partnerships that remain based on the principles of sustainability. This study contributes theoretically through the framework of sustainable tourism, the 7P Marketing Mix, and SWOT analysis in the context of developing cultural museum promotion.